Jak pogodzić perfekcjonizm i eudajmonizm z hedonizmem? Wokół utylitaryzmu j. S. Milla - Filipow, Elżbieta (Hybris, 2016)
J. S. Mill is commonly considered as a representative of psychological hedonism. However, his utilitarianism has also eudaimonic and perfectionistic aspects. Thus, various aspects are interelated with one another not only in his moral philosophy, but are present also in his political philosophy. Interpretators of Mill’s philosophy inquire: how those aspects can be reconciled and if Mill's conception can be consistent then? Main aim of the paper is to explain and justify the view, that the idea of happiness by J. S. Mill based on the greatest happiness principle is founded on both traditions present in the Ancient times: eudaimonism and hedonism. I assume, that: in philosophy of J. S. Mill, formulated in the perspective of both traditions of the idea of happiness and good life, hedonism can be reconciled with eudaimonism and perfectionsm. Philosopher can be qualified as many-sided and eclectic, thus denominating his exclusively as hedonist would be incomplete and would be a result of too hasty and imprecise reading of his works.